A review of lithium extraction from natural resources - Liu, Yubo; Ma, Baozhong; Lü, Yingwei; Wang, Chengyan; Chen, Yongqiang (International journal of minerals, metallurgy and materials, 2023)
Lithium is considered to be the most important energy metal of the 21st century. Because of the development trend of global electrification, the consumption of lithium has increased significantly over the last decade, and it is foreseeable that its demand will continue to increase for a long time. Limited by the total amount of lithium on the market, lithium extraction from natural resources is still the first choice for the rapid development of emerging industries. This paper reviews the recent technological developments in the extraction of lithium from natural resources. Existing methods are summarized by the main resources, such as spodumene, lepidolite, and brine. The advantages and disadvantages of each method are compared. Finally, reasonable suggestions are proposed for the development of lithium extraction from natural resources based on the understanding of existing methods. This review provides a reference for the research, development, optimization, and industrial application of future processes.